2000
DOI: 10.1007/s002770000236
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow microvessel density is a prognostic factor for survival in patients with multiple myeloma

Abstract: The importance of neoangiogenesis for the progressive growth and viability of solid tumors is well established. Recently, there has been growing evidence that angiogenesis might also be important in hematological malignancies, but only few data are available. In this report, we have studied the impact of bone marrow microvessel density and survival in patients with multiple myeloma (MM). Immunohistochemical CD34 stained paraffin-embedded bone marrow biopsies of 44 patients with newly diagnosed MM were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
11

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 17 publications
6
86
0
11
Order By: Relevance
“…Similar to our experience Sezar et al [20] found a significant difference in the survival of patients with low-and high-grade bone marrow microvessel density. They found that in a multivariate Cox proportional hazards model, using previously identified prognostic factors, i.e., b 2 microglobulin, C-relative protein, and age, MVD remained a significant prognostic factor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our experience Sezar et al [20] found a significant difference in the survival of patients with low-and high-grade bone marrow microvessel density. They found that in a multivariate Cox proportional hazards model, using previously identified prognostic factors, i.e., b 2 microglobulin, C-relative protein, and age, MVD remained a significant prognostic factor.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies of angiogenesis in multiple myeloma have been done [11][12][13][14][15][16][17][18][19][20][21]. All the studies done in the literature for angiogenesis in MM measured microvessel density (MVD) in the ''hot spots.''…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes are involved in the degradation of the basement membrane and the extracellular matrix, and promote the migration and proliferation of endothelial cells to form a new blood vessel (Moses, 1997;Zetter, 1998). In human MM, VEGF and bFGF are secreted by tumour cells and the concentrations of these angiogenic factors are higher in more advanced disease (Vacca et al, 1998;Bellamy et al, 1999;Dankbar et al, 2000;Di Raimondo et al, 2000;Sezer et al, 2000;. MM cells also secrete MMPs (Barillé et al, 1997(Barillé et al, , 1999Vanderkerken et al, 2000) and uPA (Hjertner et al, 2000) and their conditioned medium is able to stimulate the proliferation and migration of endothelial cells (Vacca et al, 1998(Vacca et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The human U266 MM cell line and bone marrow plasma cells from patients with active MM display a strong angiogenic potential (Vacca et al, 1998(Vacca et al, , 1999Laroche et al, 2001). Moreover, bone marrow MVD also seems to be a prognostic factor of survival in MM patients (Sezer et al, 2000).…”
mentioning
confidence: 99%
“…Sections (3 Am) of mercuric chloride -fixed paraffinembedded biopsy specimens were obtained from the posterior iliac crest of multiple myeloma and MGUS patients and healthy agematched subjects. The sections were immunostained using a monoclonal antibody against CD34, as previously described (2,6). The MVD for each biopsy was determined by counting the number of individually stained microvessels (capillaries and small venules not exceeding 10 Am) at Â200 magnification in three areas of highest vessel density according to the accredited ''hotspot'' method, as previously described (17).…”
Section: Methodsmentioning
confidence: 99%